Ionospheric spatial decorrelation assessment for GBAS daytime operations in Brazil. Issue 2 (6th May 2021) - Chang, Hyeyeon; Yoon, Moonseok; Pullen, Sam; Marini‐Pereira, Leonardo; Lee, Jiyun
Abstract: Extensive ionospheric studies were conducted to support the initial phase of system design approval for the existing SLS‐4000 GBAS installed at Antonio Carlos Jobim International Airport (formerly Galeão International Airport) (GIG) in Rio de Janeiro, Brazil. This paper focuses on determining the broadcast value of the standard deviation of vertical ionospheric gradients (or σ vig ) that is required to bound ionospheric spatial gradients in Brazil under nominal conditions during daytime hours. The time‐step method is useful for gaining sufficient samples at distances less than the physical separation distance of ground stations and was utilized to estimate ionospheric spatial gradients. A new method called "geometric similarity" was developed to estimate ionospheric temporal gradients and evaluate the temporal effect added to the bounding σ vig values. As a result, a σ vig of 13 mm/km, including a temporal gradient contribution of approximately 2 mm/km, is conservative enough to bound ionospheric spatial decorrelation for daytime GBAS operations in Brazil.